2021
DOI: 10.36401/jqsh-21-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Responses Among Healthcare Workers Providing Care for Patients with COVID-19: A Web-Based Cross-Sectional Survey in Riyadh, Saudi Arabia

Abstract: Introduction Coronavirus disease (COVID-19) is a pandemic of international concern that has caused significant physical and psychological health challenges to healthcare workers worldwide. This study aimed to assess and evaluate the psychological responses of healthcare workers who provided hands-on care for patients with COVID-19 at King Fahad Medical City (KFMC), Riyadh, Saudi Arabia, as it was converted to a dedicated COVID-19 hospital during the pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The findings of this study support that a person can perceive someone else's emotional state and be touched by the suffering of others 5,32,33 . However, from a cognition point of view, our nursing students could understand their patients' situation.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The findings of this study support that a person can perceive someone else's emotional state and be touched by the suffering of others 5,32,33 . However, from a cognition point of view, our nursing students could understand their patients' situation.…”
Section: Discussionsupporting
confidence: 66%
“…The findings of this study support that a person can perceive someone else's emotional state and be touched by the suffering of others. 5,32,33 However, from a cognition point of view, our nursing students could understand their patients' situation. This implies that a hermeneutic movement could have been represented here because this movement allowed shifting between alienation and dedication.…”
Section: Overwhelming Emotions-" I Was Too Anxious and Could Not Conc...mentioning
confidence: 99%
“…20 Depression, anxiety and stress scale was employed by various studies: Szmyd et al, 2021, this study was conducted among 2300 HCPs in Poland, its reliability was (Cronbach's α = 0.928), 2 Ozamiz-Etxebarria et al, 2020, a cross-sectional descriptive study conducted among 1003 population in northern Spain, its reliability was (α = 0.76, 0.82, and 0.75 for depression, anxiety and stress respectively), 1 and Abuzied et al, 2021, this study conducted in Riyadh, Saudi Arabia, 500 subjects were enrolled using a descriptive cross-sectional design. 21 In the current study, we determined HCPs' mental status, especially anxiety, stress, and depression in Iraq for the duration of the COVID-19 pandemic between June 18 and June 29, 2021. The results of our study showed that the majority of our participants have a normal level of depression, anxiety and stress subscales with aspect regarding vaccination with one of the COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Depression, anxiety and stress scale was employed by various studies: Szmyd et al, 2021, this study was conducted among 2300 HCPs in Poland, its reliability was (Cronbach’s α = 0.928), 2 Ozamiz-Etxebarria et al, 2020, a cross-sectional descriptive study conducted among 1003 population in northern Spain, its reliability was (α = 0.76, 0.82, and 0.75 for depression, anxiety and stress respectively), 1 and Abuzied et al, 2021, this study conducted in Riyadh, Saudi Arabia, 500 subjects were enrolled using a descriptive cross-sectional design. 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation